Alkali Additives Enable Efficient Large Area (>55 cm2) Slot‐Die Coated Perovskite Solar Modules. (19th February 2022) - Rana, Prem Jyoti Singh; Febriansyah, Benny; Koh, Teck Ming; Muhammad, Bening Tirta; Salim, Teddy; Hooper, Thomas J. N.; Kanwat, Anil; Ghosh, Biplab; Kajal, Priyanka; Lew, Jia Haur; Aw, Yeow Chong; Yantara, Natalia; et al.
Abstract: Typical fabrication methods for laboratory‐scale (<1 cm 2 ) perovskite solar cells (PSCs) are undeniably not scalable and the control of crystallization of large‐area perovskite layer for commercial sized modules is also particularly challenging. Here, a seed‐assisted crystallization approach is demonstrated through addition of alkali salts, CsPbBr3 and KPb2 Br5, to the perovskite precursor ink for enabling homogeneous and highly crystalline large‐area Cs0.15 FA0.85 Pb(I0.83 Br0.17 )3 (CsFA) perovskite films via scalable slot‐die coating technique. X‐ray photoelectron spectroscopy analysis reveals the segregation of potassium ions at SnO2 /perovskite interface which serve as nucleation sites for the crystallization of perovskite layer. The uniformly slot‐die coated CsFA films (100 cm 2 ) from the additives containing precursor inks possess larger grains with enhanced optoelectronic properties and the corresponding devices display higher reproducibility and consistency. A champion device efficiency of 18.94% under 1 sun illumination for slot‐die coated PSCs in n‐type/intrinsic/p‐type structure is demonstrated with improved stability with 82% of its initial efficiency tested at 65 °C for 1150 h. The slot‐die coated methylammonium‐free perovskite module with an active area of 57.5 cm 2 shows an efficiency of 16.22% and retains 82% of its initial efficiency after 4800 h under 30% relative humidity without encapsulation. Abstract : A seed‐assisted crystallization approach is demonstrated through addition of alkali salts for enabling homogeneous and highly crystalline large‐area perovskite films via scalable slot‐die coating technique. The slot‐die coated methylammonium‐free perovskite module with an active area of 57.5 cm 2 shows an efficiency of 16.22% and retains 82% of its initial efficiency after 4800 h under 30% RH without encapsulation.